An integrated mitigation approach to diffuse agricultural water pollution–a scoping review - Quill, Luke; Ferreira, Diogo; Joyce, Brian; Coleman, Gabriel; Harper, Carla; Martins, Marta; Hodkinson, Trevor; Trimble, Daniel; Gill, Laurence; O’Connell, David W. (Frontiers in Environmental Science, 2024)
Non-point source pollution and water eutrophication from agricultural runoff present global challenges that impact ground and surface waters. The search for a feasible and sustainable mitigation strategy to combat this issue remains ongoing. This scoping review aims to explore one potential solution by examining relevant literature on agricultural practices of the past and recent edge-of-field measures, designed to ameliorate the impacts of agricultural runoff on soil and water quality. The study focuses on integrating findings from diverse research fields into a novel myco-phytoremediation approach, which involves the synergistic relationship of plants, arbuscular mycorrhizal fungi, and plant beneficial bacteria within vegetative buffer strips. The implementation of these augmented buffer strips enhances nutrient retention in the soil, reduces runoff volume, promotes biodiversity, and increases plant biomass. This biomass can be converted into biochar, an effective sorbent that can be used to filter dissolved and particulate nutrients from surface waterways. The resulting nutrient-rich biochar can be repurposed as a form of bio-fertiliser, optimizing fertiliser consumption and subsequently reducing the depletion rate of phosphorus, a limited resource. This paper investigates a circular model of abatement of agricultural runoff via maximal nutrient retention and subsequent recycling of nitrogen and phosphorus back into the agricultural system. The key impact lies in its contribution to addressing the issue of non-point source pollution and eutrophication by encouraging multidisciplinary research aimed at solving these complex environmental issues.